Non-Biaryl Atropisomers in Organocatalysis - Brandes, Sebastian; Niess, Barbara; Bella, Marco; Prieto, Auxiliadora; Overgaard, Jacob; Jørgensen, Karl Anker (Chemistry : a European journal, 2006)
A new class of 6′‐hydroxy cinchona alkaloids, with a non‐biaryl atropisomeric functionalisation at position 5′ of the quinoline core can be prepared by an easy amination procedure. These are the first derivatives for which the principle of atropisomerism is engrafted in the classical core of the cinchona alkaloids. The aminated cinchona alkaloids are effective organocatalysts for the Michael addition of β‐keto esters to acrolein and methyl vinyl ketone, in up to 93 % ee (ee=enantiomeric excess), as well as for the asymmetric Friedel–Crafts amination of a variety of 2‐naphthols, permitting the preparation of the latter in up to 98 % ee. The aminated 8‐amino‐2‐naphthol itself is the first chiral organocatalyst based on non‐biaryl atropisomerism. The two enantiomers of this chiral primary amine can be used for the direct α‐fluorination of α‐branched aldehydes. The fluorinated compounds can thereby be accessed in up to 90 % ee. Friedel–Crafts aminations: Combine non‐biaryl atropisomerism and organocatalysis and a variety of reactions will be catalysed. These two concepts were combined in cinchona alkaloid derivatives and in chiral primary amines (see scheme). The atropisomeric compounds were then used as catalysts in Friedel–Crafts aminations (up to 98 % ee), in Michael additions (up to 93 % ee) and in fluorinations of α‐branched aldehydes (up to 90 % ee).